evaluate the following expression.
where a = 1, b = -2, and c = 0:
Now we switch the limits and switch the sign:
and that f (x) is an even function,
find the following integral.
and that f ( x ) is an even function,
We pull out the constant:
We use the fact that f is even:
You don't need to do these steps in this particular order. You could pull out the constant first, then switch the limits.
and that f is an odd function,
Pull out the constant:
Since f (x) is odd, its integral from -a = 1 to a = -1 is zero, so
Make it rain.
The who, what, where, when, and why of all your favorite quotes.